Quality of Work Life (QWL) From Psychological Perspective and The Development of Its Measurement - Bagus Riyono; Sri Hartati; Fatdina Fatdina (Jurnal Psikologi, 2022)
One strategy that can integrate the interests of the company and the interests of employees is the implementation of Quality of Work Life (QWL). This study aimed to construct a new theory of QWL from the psychological perspective and develop its standardized measuring instrument that can be used to assess the implementation of QWL as a strategy to improve employee well-being and, at the same time, increase productivity. This study was conducted in two steps. First, meta-ethnography was adopted to construct the psychological elements of QWL. Further in the second step, Confirmatory Factor Analysis (CFA) was conducted to test the construct validity of the QWL instrument. Five basic psychological constructs that represent QWL were obtained from the meta-ethnography: “trust”, “care”, “respect”, “learn”, and “contribute”, and for each construct was measured by five items. CFAof these five constructs involving 675 employees showed that the QWL instrument is valid and reliable. SEM model with five aspects consisting of five items each, fit with the research data (CFI= 0.89, RMSEA= 0.07). The QWL measuring instrument in this study is suggested to be studied further as a predictor of variables related to organizational behavior, such as job satisfaction, OCB, and work engagement.